Dietary protein and protein substitute requirements in adults with phenylketonuria: A review of the clinical guidelines. Issue 3 (March 2021) - Firman, Sarah; Witard, Oliver C.; O'Keeffe, Majella; Ramachandran, Radha
Summary: Lifelong dietary treatment is recommended in the management of phenylketonuria (PKU). Accordingly, an increasing adult population require age-specific PKU guidelines on protein requirements to support changing metabolic demands across the lifespan. Given that protein intake for dietary management of PKU is primarily (52–80%) derived from protein substitutes, the prescribing practice of protein substitutes must be underpinned by robust evidence. Whilst dietary guidelines for PKU management is evolving to incorporate adult specific protein recommendations, the scientific evidence underpinning these guidelines is currently limited. Instead, the determination of protein requirements for people with PKU have previously been extrapolated from estimates derived from the general healthy population, based on arguably outdated nitrogen balance methodology. Furthermore, a compensatory factor of 20–40% has been incorporated to account for the reduced uptake and utilisation of the elemental amino acids contained in protein substitutes. However, research informing this compensatory factor has been conducted in younger adults, with the majority of studies in non-PKU individuals. Given extensive evidence that the muscle anabolic response to ingested protein is impaired in older vs. young adults, the validity of current dietary protein recommendations for adults and older adults with PKU has been challenged. This narrative review aims to critically evaluate the existing scientific evidence underpinning current guidelines on protein requirements for adults with PKU, highlighting existing gaps in knowledge and directions for future research. We argue that current guidelines on protein requirements need updating to optimise long-term physical and functional outcomes in older adults with PKU.